Online Child Sexual Abuse: Exploring Psychological And Social Impacts, Prevention, And Intervention Strategies - Hamdi Bacha , Yasmine (مجلة دراسات في سيكولوجية الانحراف, 2024)
Abstract This research paper examines the profound psychological and social consequences experienced by victims of online child sexual abuse. It sheds light on the prevalence and impacts of online child sexual abuse, including grooming, sextortion, and the production and distribution of child sexual abuse material. The psychological consequences encompass a range of issues such as post-traumatic stress disorder (PTSD), depression, anxiety disorders, disrupted attachment, sexual dysfunctions, self-esteem issues, and an increased risk of suicidal ideation. Social consequences include stigmatization, victim blaming, social isolation, educational disruptions, and strained familial relationships. The study explores the challenges faced by victims in seeking support and recovery and provides insights into prevention and intervention strategies. It emphasizes the need for legislative measures, international cooperation, education campaigns, victim-centered approaches, and research and data collection. Overall, this research highlights the necessity of a comprehensive and collaborative approach to effectively combat online child sexual abuse and safeguard the well-being of victims.